Formation of system frameworks of energy controlling - Kovalev, Anatoliy; Degtiareva, Olga (Technology audit and production reserves, 2017)
The object of research is the controlling concept and its application in the energy sector of the enterprise. Controlling concept opens wide perspectives and provides economic instruments to raise effectiveness and to reach goals of enterprise. The main challenge by implementation of controlling concept in energy sphere is lack of understanding of all opportunities that controlling concept gives as well as needs of its integration on all levels of decisions making. As far as the controlling is illustrious by its system approach, the system frameworks of energy controlling cover multifunctional areas and managerial systems of enterprise. The operational cycle of energy controlling is described. This cycle includes the main stages of management of energy consumption in the enterprise. The system frameworks of energy controlling are formed. Being a part of the general controlling mechanism, energy controlling integrates into the control and analytical work of the enterprise for achievement of energy goals. By its conceptual basement, it provides: – transparency of processes and results in energy sector; – timely information and analytical support for both operational and strategic decisions related to energy activity and development; – optimization of allocation of companies internal resources for enhancement of energy efficiency and energy saving; – coordination of energy goals and objectives at all levels of management, as well as a systematic, integrated solution of energy problems.